From Interference to Fluency: Analysing Indonesian Students' Progress in English Oral Communication - Susanto, Susanto; Nanda, Deri Sis; Rafik-Galea , Shameem; Supasa, Aprilia Yunda (Elsya : Journal of English Language Studies, 2023)
This study examines the progress of Indonesian students in spoken English through a task-based approach in an EFL classroom. The aim of the study is to identify communication strategies and linguistic aspects used by the students during oral interaction and production. The data collected from 50 Indonesian students attending a Phonetics and Phonology course at Universitas Bandar Lampung was analyzed using triangulation with class diary and self-assessment questionnaires. The findings show significant improvements in oral interaction and production, including negotiation, cooperation, mediation, intonation, fluency, pronunciation, and rhythm. However, the students made less effort to intervene in the spoken code of the interlocutor and their own interlanguage. The study recommends training tasks that emphasize paraphrasing and self-improvement of oral discourse to enhance their overall oral proficiency in English. The findings of this study have important implications and provides a promising framework for improving students' communication strategies and linguistic aspects. Therefore, these findings suggest that effective language teaching should prioritize not only linguistic aspects but also communication strategies that enable effective oral interaction. This study's recommendations could be useful for language educators worldwide seeking to enhance their students' overall oral proficiency in English.